Building tribal communities in the collaborative economy: an innovation framework. (2nd April 2016) - Barnes, Stuart J.; Mattsson, Jan
Abstract: In recent years, there has been a groundswell of initiatives aimed at providing platforms to share resources among people. Collaborative consumption provides a model for a 'sharing economy' where the dominant logic of consumers is resource access rather than ownership. This study examines the nature and development of a variety of collaborative consumption businesses; in particular, we explore how start-up entrepreneurs see the problems of creating a tribal community among customers and users. Interviews were carried out with founders and co-founders of collaborative consumption ventures during 2014–15. The results suggest that these organisations face many common issues. We develop and apply a framework to understand some of these. We find that collaborative consumption entrepreneurs strive to build a tribal community by matching, in an innovative way, supply and demand. This is typically done by co-creating shared commonality, developing scalable electronic platforms, and building trust into platforms using social media to develop proxy social capital. Consequently, by using existing ecosystems of social media, tribal communities can be formed and scaled much more quickly than via traditional marketing approaches.